Non-Astronomical Aspects of the Success of Rukyatul Hilal in East Java - Mulyadi, Achmad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The success of rukyatul hilal (moon sighting) is not only influenced by the physical aspects of the hilal (the crescent moon), but also depends on non-physical (non-astronomical) aspects. In the last 5 years, 7 out of 23 locations in East Java have contributed to sighting the hilal while other locations have experienced failures due to various constraints and obstacles. This paper evaluates these locations using geographical and topographical theories to delve into three main questions: the implementation of rukyatul hilal activities in East Java, the influence of geographical and topographical conditions of the locations, and the mapping of rukyatul hilal locations in East Java. Research data were measured and observed directly and indirectly using Google Earth with area sampling and non-probability sampling techniques. Research findings reveal that: first, rukyatul hilal is carried out at the beginning of each Hijri month by most observers at several locations during important months such as Ramadan, Shawwal, and Dhul Hijjah with the naked eye, while other locations use optical aids with low success rates; second, geographically, most rukyatul hilal locations in East Java are located near the equator with the main obstacle being disturbances from fog pollution, dust, clouds, rain, and other atmospheric particles; and third, out of 23 active rukyatul hilal locations in East Java mapped: a) locations categorized as observatories, with two observatories that do not fully contribute to moon observations, b) other hilal observation locations categorized as locations located on the north and south coast, with five locations that do not fully contribute to hilal observations, and c) other hilal observation locations categorized as locations located at high altitudes, with seven locations contributing to the implementation of hilal sighting and three locations dominating the production of hilal visibility more than once.